History of knowledge and evolution of occupational health and regulatory aspects of asbestos exposure science: 1900–1975. (21st April 2017) - Barlow, Christy A.; Sahmel, Jennifer; Paustenbach, Dennis J.; Henshaw, John L.
Abstract: The understanding by industrial hygienists of the hazards of asbestos and appropriate ways to characterize and control exposure has evolved over the years. Here, a detailed analysis of the evolution of industrial hygiene practices regarding asbestos and its health risks, from the early 1900s until the advent of the national occupational health and safety regulatory structure currently in place in the US (early-to-mid 1970s) is presented. While industrial hygienists recognized in the early 1900s that chronic and high-level exposures to airborne concentrations of asbestos could pose a serious health hazard, it was not until the mid-1950s that the carcinogenic nature of asbestos began to be characterized and widespread concern followed. With the introduction of the membrane filter sampling method in the late 1960s and early 1970s, asbestos sampling and exposure assessment capabilities advanced to a degree which allowed industrial hygienists to more precisely characterize the exposure–response relationship. The ability of industrial hygienists, analytical chemists, toxicologists, and physicians to more accurately define this relationship was instrumental to the scientific community's ability to establish Occupational Exposure Levels (OELs) for asbestos. These early developments set the stage for decades of additional study on asbestos exposure potential and risk of disease. This was followed by the application of engineering controls and improved respiratory protection which, over the years, saved thousands of lives. This paper represents a state-of-the-art review of the knowledge of asbestos within the industrial hygiene community from about 1900 to 1975.